Penguatan Tata Kelola Pemerintah dan SDM Adaptif Digital Guna Percepatan Reformasi Birokrasi di Kelurahan-Kelurahan Kecamatan Pontianak Selatan, Kota Pontianak, Provinsi Kalimantan Barat - Azharisman Rozie; Dwi Agus Sumarno; Riko Wijaya; Hendayana Hendayana (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
This community service activity aims to strengthen government governance and adaptive digital human resource (HR) capacity of civil servants (ASN) in sub-districts of South Pontianak District, Pontianak City. The main problems identified through preliminary surveys were the low awareness and willingness of apparatuses to adapt to digital technology, as well as the absence of standardized operating procedures (SOPs) in internal administrative governance. Methods employed included reflective discussion, interactive lectures and discussions, and SOP drafting assistance. Evaluation was conducted using the CIPP model (Context, Input, Process, Product) along with pre-test and post-test instruments comprising 20 questions. The activity involved 18 apparatuses representing five sub-districts (Banua Melayu Darat, Banua Melayu Laut, Akcaya, Kota Baru, and Parit Tokaya) and one district representative. Results showed an increase in participants' average score from 75.00 (pre-test) to 86.47 (post-test), representing a 16% improvement. Additionally, the activity produced five internal administrative SOP documents and a Follow-Up Action Plan (RKTL) from each sub-district as a commitment to digital transformation implementation. In conclusion, education-based intervention and technical assistance proved effective in improving sub-district apparatus competency in supporting digital bureaucratic reform.